2022
DOI: 10.3390/ijerph19084925
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mixed-Gender Competition: Choking under Pressure in a Dynamic Tournament

Abstract: In sports, there has been a recent and active movement to promote mixed-gender competitions for achieving gender equality in the field. However, the current debate regarding its effects limitedly focuses on balancing the number of opportunities for females and neglects its effect on athlete performance. To address this gap, this study investigated whether and how mixed-gender competitions mitigate gender-specific disadvantages of interim leaders in dynamic tournaments from the perspective of choking under pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…In both Cohen-Zada et al (2017) and Bühren et al (2024) studies, researchers found males to be more susceptible to choking due to performance pressure. Contrastingly, Min (2022) found high level female athletes to underperform in pressurized competitive situations compared to males in segregated, but not mixed-gender competition.…”
Section: Introductionmentioning
confidence: 72%
“…In both Cohen-Zada et al (2017) and Bühren et al (2024) studies, researchers found males to be more susceptible to choking due to performance pressure. Contrastingly, Min (2022) found high level female athletes to underperform in pressurized competitive situations compared to males in segregated, but not mixed-gender competition.…”
Section: Introductionmentioning
confidence: 72%
“…Men have 15- to 20-fold greater circulating testosterone than women which influences performance [ 23 ], but also possibly affects the injury panorama. Differences in psychological factors may also have an impact [ 29 ]. Those considerations call for further studies on elite women athletes, introducing different methodological approaches [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, differences in phycological factors have an impact. 26 All this calls for separate studies for women elite athletes with sometimes different methodological considerations. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Men have 15-fold to 20-fold greater circulating testosterone than women which influence performance25 and possibly affects the injury panorama. Furthermore, differences in phycological factors have an impact 26. All this calls for separate studies for women elite athletes with sometimes different methodological considerations 27…”
Section: Discussionmentioning
confidence: 99%